The Politics of Sex and Other Essays - Grant, R. author. aut Link
XVII, 248 p.
Keywords: These essays cover topics as radically diverse as Charles Rennie Mackintosh, Václav Havel, The Magic Flute and Viz magazine. All have been published before, and many have already proved controversial. The author, a leading Oakeshott scholar, contributes frequently to the TLS . Witty, moving and erudite, his prose is also conspicuously graceful and clear. This collection is addressed as much to the educated general reader as to the academic specialist. It includes an otherwise almost unobtainable exchange with Sir Isaiah Berlin.